Intimate partner violence during pregnancy and adverse birth outcomes: a case-control study - Eskedar Berhanie; Dawit Gebregziabher; Hagos Berihu; Azmera Gerezgiher; Genet Kidane (BMC, 2019)
Abstract Background Intimate partner violence is a common phenomenon in Ethiopia families. About 81% of women believed that a husband is justified in beating his wife. About 30-60% of families were affected by their intimates. Women suffer physical, emotional, sexual and economic violence by their intimate partners. It often remains either for the sake of family secrecy, cultural norms or, due to fear, shame and community's reluctance on domestic affair and social stigma.The objective of this study is to examine the association between intimate partner violence during pregnancy and adverse birth outcomes. Methods A hospital based unmatched case control study was conducted in four zonal hospitals of Tigray region. A total of 954 study participants (318 cases and 636 controls) were taken. Systematic sampling was used to select the cases and controls. Ethical clearance was obtained throughout the study period. Result Out of 954 interviewed mothers, 389 (40.8%) had experienced intimate partner violence during their index pregnancy period. More than two third (68.6%) of cases had been exposed to intimate partner violence. Multivariable logistic regression analysis showed that, women exposed to intimate partner violence during pregnancy were three times more likely to experience low birth weight (AOR = 3.1; CI 95% [1.470,6.618]) and preterm birth (AOR = 2.5; CI 95% [2.198-2.957]). It was observed that women who had been exposed to physical violence during pregnancy were five times more likely to experience low birth weight (AOR = 4.767; CI 95% [2.515, 9.034]) and preterm birth (AOR = 5.3; CI 95%: 3.95-7.094). Conclusion and recommendation It was found that the risk of preterm birth and low birth weight was increased when the pregnant women were exposed to more than one type of intimate partner violence and physical violence during pregnancy. Therefore, Efforts to address maternal and newborn health need to include issues of violence against women.